2022
DOI: 10.1177/17455057221142369
|View full text |Cite
|
Sign up to set email alerts
|

Virtual group-based mindfulness program for autistic women: A feasibility study

Abstract: Background: Autistic women experience life differently than autistic men. For example, autistic women tend to be diagnosed significantly later than autistic men, they experience a higher number of traumas, and are at increased risk for mental health conditions. Given gender-specific life experiences, autistic women may benefit from gender-specific group-based supports. Virtual mindfulness has been shown to be helpful in improving well-being among autistic adults; however, limited research has explored the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Despite the potential benefits of online mental health programs, little research has explored their utilization among autistic individuals ( Gaigg et al, 2020 ; Lunsky et al, 2022 ; Redquest et al, 2022 ), particularly concerning self-guided self-compassion concepts (Cai et al, this issue). Initial investigations indicate the potential of virtual mindfulness programs for autistic adults, though existing programs have predominantly relied on sessions with facilitators ( Lunsky et al, 2022 ; Redquest et al, 2022 ). Gaigg et al (2020) found promising results with online self-guided CBT and MBT tools in reducing anxiety among autistic adults.…”
mentioning
confidence: 99%
“…Despite the potential benefits of online mental health programs, little research has explored their utilization among autistic individuals ( Gaigg et al, 2020 ; Lunsky et al, 2022 ; Redquest et al, 2022 ), particularly concerning self-guided self-compassion concepts (Cai et al, this issue). Initial investigations indicate the potential of virtual mindfulness programs for autistic adults, though existing programs have predominantly relied on sessions with facilitators ( Lunsky et al, 2022 ; Redquest et al, 2022 ). Gaigg et al (2020) found promising results with online self-guided CBT and MBT tools in reducing anxiety among autistic adults.…”
mentioning
confidence: 99%